KARAKTERISTIK PASIEN STROKE ISKEMIK DI RUMAH SAKIT UMUM DAERAH Dr. H. CHASAN BOESOIRIE TERNATE - Farhan Syahti M S; Nur Upik En Masrika (Fakultas Kedokteran, Universitas Khairun, 2020)
Stroke is known as a health problem that causes the second death and as the third cause ofdisability in the world. The purpose of this study was to determine the characteristics of ischemic strokepatients from January- December 2019 at regional public hospital Dr. H. Chasan Boesoirie Ternate. Thedesign of this study was a retrospective descriptive study with a cross-sectional approach. Using totalsampling techniques. The sample in this study were all stroke patients at Regional Public Hospital Dr. H.Chasan Boesaoirie who met the inclusion and exclusion criteria for the January-December 2019 period.The results showed that the majority of ischemic stroke patients suffered by 62% of men, with avulnerable age around 51-60 years with a percentage of 50%. Having a total cholesterol level close tonormal 50%, LDL levels close to normal 50%, HDL levels close to normal 50%, normal TGA levels 69%.From the results of the study it can be concluded that the majority of stroke cases obtained at RegionalPublic Hospital Dr. H. Chasan Boesoirie is an ischemic stroke, male sex, age group 51-60 years and theresults of lipid profiles in this study are still largely at near normal levels.